2013
DOI: 10.1089/cap.2012.0019
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Long-Acting Medications on Attention-Deficit/Hyperactivity Disorder Treatment Disparities

Abstract: Objective: Long-acting stimulants have increased medication adherence for many children diagnosed with attention deficit/hyperactivity disorder (ADHD), but it is unknown whether the increase has been similar across racial/ethnic groups. Our objective was to determine whether differences in medication utilization and adherence among white, black, and Hispanic ADHD-diagnosed children and adolescents narrowed following the introduction of long-acting stimulants in the 1990s. Methods: We conducted a retrospective … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 18 publications
1
11
0
Order By: Relevance
“…Consistent with previous studies, 18,19 there were considerable racial/ ethnic differences in medication discontinuation. Higher rates of medication discontinuation among minority youth could be due to differences in cultural health beliefs and/or concerns about ADHD medication treatment.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Consistent with previous studies, 18,19 there were considerable racial/ ethnic differences in medication discontinuation. Higher rates of medication discontinuation among minority youth could be due to differences in cultural health beliefs and/or concerns about ADHD medication treatment.…”
Section: Discussionsupporting
confidence: 90%
“…14 Yet, rates of ADHD medication adherence and persistence are low among Medicaidenrolled youth in general, 15 -18 and even lower among African American and Hispanic children than non-Hispanic white children. 18,19 Lower rates of ADHD medication persistence among minority youth compared with whites are most problematic if racial/ethnic minorities are also more likely to disengage from treatment entirely. Randomized trials have revealed that behavioral therapy is also effective at reducing ADHD symptoms.…”
mentioning
confidence: 99%
“…The analysis showed low adherence as the main theme. Latino children were less adherent to medication than other groups (Adeyemi, Rascati, Lawson, & Strassels, 2012; Bhatia et al, 2012; Capo-Ramos, Duran, Simon, Akinbami, & Schoendorf, 2014; Herndon, Mattke, Cuellar, Hong, & Shenkman, 2012; Makhinova, Barner, Richards, & Rascati, 2015; McQuaid et al, 2012; Mosnaim et al, 2014; Palli, Kamble, Chen, & Aparasu, 2012; Saloner, Fullerton, & McGuire, 2013). Adeyemi et al (2012) described adherence to oral diabetic medication and assessed trends in adherence and persistence using medication possession ratio (MPR) and persistence as a proxy for measuring adherence.…”
Section: Resultsmentioning
confidence: 84%
“…In previous studies, most had observation period up to 1 year ( 22 ). Until the current study, the longest treatment duration was 6 years for treatment discontinuation and 2 years for adherence ( 23 24 ).…”
Section: Discussionmentioning
confidence: 97%